SEJARAH TRANSFORMASI PENDIDIKAN ISLAM DI INDONESIA - Ma’mum Aly (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2019)
This paper examines the history of the transformation of Islamic education in Indonesia according to Ariel Furchan. As a study of literature, then this article refers to the work of Ariel Furchan titled Transformation of Islamic Education in Indonesia: Anatomy Existence Madrasah and PTAI. However, this study is the discussion about Islam in general education from the historical aspect before the colonial Dutch, the Dutch colonial era occur until after the independence of the Republic of Indonesia. The conclusions from this discussion is that the Islamic education of transformation occurred as a result of the dialectic of Islamic education with a phenomenon that occurs or context, both Dutch-style education system, as well as the presence of the Indonesian Communist Party, and even the challenges of globalization and the character of the nation itself. The transformation of Islamic education should be accompanied by the availability of qualified human resources, so that the transformation of Islamic education can work together in every process.